Comprehensive Comparative Study of Dental Composites: Types, Properties, and Applications in Dental Technology - Khaled Elgergeni; Hanan Ajaj; Rowaida Daoa; Marya Mustafa (AlQalam Journal of Medical and Applied Sciences, 2025)
This study evaluates the mechanical, physical, and biological performance of three principal categories of dental composites—nanofilled, microhybrid, and bulk-fill—while tracing their historical evolution and clinical relevance. Standardized laboratory tests assessed compressive strength, flexural strength, polymerization shrinkage, three-body wear resistance, water absorption, and surface roughness following artificial aging. In vitro cytotoxicity was analyzed using L929 fibroblast cultures. A comprehensive literature review was incorporated to contextualize experimental findings. Results revealed that nanofilled composites excelled in surface polish retention and wear resistance, microhybrids demonstrated superior initial mechanical strength, and bulk-fill composites significantly minimized shrinkage stress. All tested materials exhibited acceptable biocompatibility. Selection of composite type should align with specific clinical priorities—whether esthetic durability, load-bearing performance, or stress reduction—highlighting the distinct advantages each category offers.